Hubungan Sosial Budaya terhadap keberhasilan Pemberian ASI Ekslusif Di Wilayah Kerja Puskesmas Waembeleng, Manggarai, NTT - Eufrasia Prinata Padeng; Putriatri Krimasusini Senudin; Dionesia Octaviani Laput (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Exclusive breastfeeding is the best food for babies. The main problem in exclusive breastfeeding is socio-culture, namely in the form of habits and beliefs of a person, especially mothers in terms of exclusive breastfeeding. The main objective of this research is to see the socio-cultural relationship with the success of exclusive breastfeeding in the working area of the Waembeleng Community Health Center, Manggarai, NTT. This research is a quantitative study with a descriptive correlation method using a cross-sectional approach. The sample size is 55 people who were selected by total sampling. The instrument used was a closed questionnaire and analyzed using the Chi-square test. The results of this study indicate that there is a socio-cultural relationship to exclusive breastfeeding because it has a p value = 0.011 (p <0.05). From the univariate results, it was found that most of the respondents aged 20-35 years were 94.6%, with an elementary school education background of 72.8%. Based on the results of this study, it is hoped that mothers under five will increase their knowledge about exclusive breastfeeding by attending counseling and actively participating in posyandu every month so that they always get knowledge about exclusive breastfeeding